Pengembangan Lembaga Kemasyarakatan: PAMPENA dan DTA Assalam Kelurahan Cigantang Kecamatan Mangkubumi melalui pendekatan aspek manajemen pengelolaan dan aspek hukum kelembagaan - Salgangga, Selji Salgangga; Fadilah, Mohamad Fazar; Arif, Arfi; Asyiah, Ai Kusmiati; Karmila, Mila; Yusnita, Rita Tri; Al Zahra, Salsabila; Hakim, Gisan Hilman (IKIP SILIWANGI, 2025)
ABSTRACT In social life, of course, every individual will try to fulfill their life needs, one of which is educational facilities and clean water provision. In an effort to meet the needs of the community, they have independently formed community organizations that operate in the field of non-formal education and clean water supply groups. However, in operational activities there are problems or obstacles that hinder the progress of the institution.The problems faced by these social institutions are:1. Management aspect of organizational management, which does not yet have an ideal organizational structure, governance, financial recording, risk management so it is difficult to develop.2. Aspects of legal legality, as a legal entity to oversee the activities of the social institution.Based on the problems found, we see the need to provide assistance through an organizational management approach consisting of HRM, Operational Management, Financial Management/Financial Recording and forming a legal entity that oversees the social institution. So that the community institution has a strategic plan and good management and has a legal entity that oversees the development of the community institution which has an impact on the benefits that are increasingly felt by the surrounding community. Keywords: Community Institutions, Legal Aspects, Management